BADAN USAHA MILIK DESA (BUMDES) IJEN LESTARI SEBAGAI INOVASIPELAYANAN PUBLIK UNTUK MENDUKUNG PENGEMBANGAN EKONOMILOKAL MELALUI COMMUNITY BASED TOURISM - Novandi, Harod Rahmad; Adi, Isbandi Rukminto (Jurnal Ilmu Kesejahteraan Sosial, 2019)
The proportion of rural poverty is always higher than urban poverty in Indonesia. Poverty reduction programs, especially in rural areas, should put the community as the priority subject in each program. Banyuwangi Regency in East Java Province is one of the best example in poverty reduction program. Banyuwangi succeed to reduce its poverty rate significantly from tourism sector. This tourism increases income per capita of Banyuwangi from year to year. The poverty reduction in Banyuwangi is influenced by smart kampung and local economic development through a community-based tourism. (CBT) and Initiating local industry.Based on observation and in depth interview, Village-Owned Enterprises (BUMDes) Ijen Lestari is an innovation for public services contributes to the community by giving loan fund to finance local economic activities and employment. BUMDes also provides services and a media for positive change and interaction. Thesis research, it is concluded that BUMDes gives positive impacts to provision of employment and tourism business income. However, as an innovation of public services, BUMDes also needs to enhance its networking with other stakeholders in order to develop its strategic destinations and improve the skills of their local human resources for using Information Technology to attract the tourists attention